2018
DOI: 10.1038/s41598-018-26442-0
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β concentrations and activity are down-regulated in the aqueous humor of patients with neovascular age-related macular degeneration

Abstract: Controversy still exists regarding the role of the TGF-β in neovascular age-related macular degeneration (nAMD), a major cause of severe visual loss in the elderly in developed countries. Here, we measured the concentrations of active TGF-β1, TGF-β2, and TGF-β3 by ELISA in the aqueous humor of 20 patients affected by nAMD, who received 3 consecutive monthly intravitreal injections of anti-VEGF-A antibody. Samples were collected at baseline (before the first injection), month 1 (before the second injection), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…All three TGF-β isoforms were detected in aqueous and vitreous humor of the human eye ( Figure 2 ), and it was determined that approximately 87% of the vitreal TGF-β is in the latent form [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Although different detection methods were used to measure TGF-β concentrations, all studies agree that TGF-β2, both active and latent, is the predominant isoform in normal aqueous and vitreous humor, and that active TGF-β1 is not detectable [ 33 , 37 , 39 , 40 ]. In human aqueous humor, the ratio among the three active isoforms was estimated to be 1:0.4:0 for β2:β3:β1, respectively [ 39 ].…”
Section: Tgf-β Synthesis and Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…All three TGF-β isoforms were detected in aqueous and vitreous humor of the human eye ( Figure 2 ), and it was determined that approximately 87% of the vitreal TGF-β is in the latent form [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Although different detection methods were used to measure TGF-β concentrations, all studies agree that TGF-β2, both active and latent, is the predominant isoform in normal aqueous and vitreous humor, and that active TGF-β1 is not detectable [ 33 , 37 , 39 , 40 ]. In human aqueous humor, the ratio among the three active isoforms was estimated to be 1:0.4:0 for β2:β3:β1, respectively [ 39 ].…”
Section: Tgf-β Synthesis and Signaling Pathwaymentioning
confidence: 99%
“…Although different detection methods were used to measure TGF-β concentrations, all studies agree that TGF-β2, both active and latent, is the predominant isoform in normal aqueous and vitreous humor, and that active TGF-β1 is not detectable [ 33 , 37 , 39 , 40 ]. In human aqueous humor, the ratio among the three active isoforms was estimated to be 1:0.4:0 for β2:β3:β1, respectively [ 39 ]. Immunolocalization of TGF-β isoforms in the anterior segment of the eye has evidenced that TGF-β1 is found in the superficial limbal epithelium, in the proximal portion of ciliary processes and in the wall of blood vessels within the ciliary body ( Figure 2 a) [ 41 ].…”
Section: Tgf-β Synthesis and Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“… 63 This family of proteins also has been found to be downregulated in the aqueous of patients with neovascular AMD. 64 TGF-β also has a critical role in immune homeostasis, as dysregulation of this signaling pathway is related to inflammatory diseases and the development of tumors. 65 , 66 Another top-ranked but smaller pathway was digestion and absorption, which refers to digestion of fats, carbohydrates, and proteins in the intestine and movement of the products of digestion out of the lumen of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The only soluble mediators associated with these 8 pathways (and therefore measurable in AH) are VEGFA, TGFβ1 and Gremlin-1, an inhibitor of TGFβ pathway. Since we recently showed that TGFβ1 is poorly expressed in the AH [ 34 , 35 ], we decided to measure VEGFA concentration. Additionally, GO analysis identified a direct validated regulation of miR-199a-3p on F11 receptor, which has been shown to be involved in the maintenance of the retinal pigment epithelium barrier [ 36 ].…”
Section: Discussionmentioning
confidence: 99%